The Expansion of the Peer Adviser Workforce: Opportunities and Challenges for Social Work. Issue 2 (2nd April 2020) - Tseris, Emma
ABSTRACT: Peer adviser roles are becoming an increasingly common—and celebrated—aspect of agencies where social workers are located. This article reports on a qualitative research study exploring the experiences of staff within a homelessness outreach service in which three peer advisers (people with a lived experience of homelessness) commenced employment. Drawing on action research principles, the study explored the experiences of the peer advisers and the broader team following the introduction of the peer adviser roles. Themes identified include, realising the skills of peer advisers, defining the role, taking a "whole of team" approach, and reflecting on power. This study demonstrates that the introduction of peer adviser roles into human service organisations is a promising strategy for creating services that are more likely to respond effectively to the needs of service users. However, social workers need to be aware of the pitfalls of tokenism and the devaluing of experiential knowledge. IMPLICATIONS Peer advisers in health and welfare agencies add significant benefits to an agency's capacity to respond to the needs of service users. The introduction of the peer workforce is aligned to social work values of service user empowerment and the valuing of experiential knowledge. In order to avoid tokenism, the introduction of peer adviser roles should be supported by both the attitudes and actions of other staff members, as well as organisational support structures.